2013
DOI: 10.1111/mmi.12389
|View full text |Cite
|
Sign up to set email alerts
|

Trapping and visualizing intermediate steps in the mismatch repair pathway in vivo

Abstract: SummaryDuring mismatch repair, MutS is responsible for mismatch detection and the recruitment of MutL to the mismatch through a mechanism that is unknown in most organisms. Here, we identified a discrete site on MutS that is occupied by MutL in Bacillus subtilis. The MutL binding site is composed of two adjacent phenylalanine residues located laterally in an exposed loop of MutS. Disruption of this site renders MutS defective in binding MutL in vitro and in vivo, while also eliminating mismatch repair. Analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 63 publications
(138 reference statements)
2
32
0
Order By: Relevance
“…Our previous research investigating MutS1 has shown that B. subtilis MutS1-GFP forms foci that are recruited to the site of DNA synthesis (25)(26)(27)(28)48). Further, homologous recombination proteins and nucleotide excision repair proteins have been shown to form foci and localize to the nucleoid, respectively, following MMC treatment (44,49).…”
Section: Together These Results Indicate That the C-terminal Smr Dommentioning
confidence: 99%
See 2 more Smart Citations
“…Our previous research investigating MutS1 has shown that B. subtilis MutS1-GFP forms foci that are recruited to the site of DNA synthesis (25)(26)(27)(28)48). Further, homologous recombination proteins and nucleotide excision repair proteins have been shown to form foci and localize to the nucleoid, respectively, following MMC treatment (44,49).…”
Section: Together These Results Indicate That the C-terminal Smr Dommentioning
confidence: 99%
“…For live imaging experiments, a plate grown overnight at 30°C was washed using S7 50 minimal medium supplemented with 2% glucose essentially as described previously (25,26,59). The OD 600 was measured and cells were diluted to an OD 600 of 0.1.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Shown are bar graphs representing the spontaneous mutation rate (Ϯ95% confidence intervals) using the MSS maximum-likelihood method, as described previously (31,63,(67)(68)(69). (A) Number of mutations per generation for wild-type strain PY79 and the ⌬recD2 and ⌬mutSL strains from at least 50 independent cultures plated on rifampin; (B) number of mutations per generation of the PY79, ⌬recD2, and ⌬mutSL strains from at least 20 independent cultures plated on trimethoprim; (C) number of mutations per generation of the indicated strains plated on rifampin.…”
Section: Fig 2 Deletion Of Recd2 Increases Spontaneous Mutagenesis Inmentioning
confidence: 99%
“…After recognizing a mismatch, MutS exchanges bound ADP for ATP and recruits MutL (1, 15). This MutS-MutL interaction is required for MutS to release the mismatch (16). MutS[K608A], which lacks detectable nucleotide binding activity, failed to localize to the replication fork, demonstrating that, at a minimum, mismatch detection by MutS requires its interaction with both β-clamp and nucleotide cofactor.…”
mentioning
confidence: 99%